Linguistic minorities and modernity : a sociolinguistic ethnography - Heller, Monica (Advances in sociolinguistics., 2006)
The subject of this book is linguistic minorities, and how language is used by speakers of languages which are not the main language of communication. This is a core topic for sociolinguists, who examine how language is actually used within a given context. Globalization, migration, and the erosion of nationhood is creating far more linguistic minorities as society becomes increasingly pluralistic. One of the major sites of contact between languages is the school, and this book focuses on linguistic interaction within this educational context. Through a careful examination of the language prac.